Effects of Temperature on Rubber (Hevea Brasiliensis Muell.-Arg.) Seed Storage - Mohd Noor, Normah (1987)
The effects of temperature on the storage of Hevea seeds and embryonic axes were studied. The first part of the study was on the effects of temperature (la, 22 and 27°C) on physiological, biochemical and structural changes during imbibed storage of Hevea seeds. The second part of the study involved the effects of temperature (la, 22 and 27°C) on storability of Hevea seeds using a modified imbibed storage method incorporating the application of 10 percent and 20 percent concentrations of a germination inhibitor (PEG) and a dry storage method in the presence of a fungicide (0.3 percent Benlate). The third part of the study was on in vitro storage of Hevea embryonic axes including a slow growth method (at 10 , 15, 18 and 20°C) and cryopreservation in liquid nitrogen (-196°C).